Centaurea breviceps Iljin (Asteraceae, Magnoliophyta): neotype and its annotation according to ITS1 and ITS2 secondary structures (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Neotype for endemic species Centaurea breviceps Iljin (section Pseudophalolepis), which grows in the south of Ukraine, was chosen based on a material from a locus classicus. The sequences and secondary structures of the internal transcribed spacers (ITS) 1 and 2 were annotated. It has been shown that C. breviceps differs from all previously sequenced species of the Acrolophus, Maculosae, Phalolepis and Pseudophalolepis sections by the unique base change in the first helix of ITS2 (C > T, site 41). Within this group of sections, C. breviceps belongs to ribotype "A" represented by diploid and autopolyploid species but not allopolyploids. C. breviceps differs from the three sequenced species of the Pseudophalolepis section (C. pseudoleucolepis, C. protogerberi and C. donetzica) by the secondary structure of ITS1 second helix and ITS2 first helix.
Keywords: Pseudophalolepis, Centaurea breviceps, neotype, endemic species, ITS1 & ITS2 secondary structures, Ukraine.